The Future of Group Decision Support System Supported Meetings: Perceiving the Value and the Need for Competitive Strategies - Al Shishany, Amer; Kharabsheh, Radwan; Elnsour, Waed; Adams, Jackson (International Review of Management and Marketing, 2017)
Conducting meetings using Group Decision Support System (GDSS) applications, as a method for brainstorming and decision-making sessions in organizations, has not yet been disseminated and adopted by the majority of either businesses or public sectors. Observations and statistics from the field indicate that organizations have scant interest or no perception at all of this approach for decision-making process. This paper is devoted to investigate the reasons behind the lack of GDSS supported meetings' adoption and, therefore, dissemination by both private and public organizations. It, also, suggests solutions for overcoming challenges encountering GDSS supported meetings' industry. The paper reports on the results of a field study of 22 semi-structured intensive interviews conducted with users of GDSS meeting software, experienced facilitators, technical support experts and managers of GDSS meeting facilities. The research took place in real business environmental settings with interviewees whom used ‘FacilitatePro', ‘MeetingSphere' and "Spilter" GDSS meeting software. Keywords: Group Decision Support Systems; Competitive Strategies; Marketing. JEL Classifications: C44, D7, M31